Vision awareness training for health and social care professionals working with people with intellectual disabilities: Post-training outcomes. (September 2015) - Dick, Joanne; Finlayson, Janet; Neil, June; Mitchell, Linda; Robinson, Nicola
People with intellectual disabilities are 10 times more likely to have a visual impairment, compared to the wider population, yet lack of awareness of their particular vision needs among health and social care professionals can act as a barrier to accessing appropriate care and treatment. Vision awareness training was delivered to 104 health and social care professionals who work with people with intellectual disabilities over a 12-month period. In all, 90 (87%) completed pre- and post-training questionnaires, using repeat measures, to determine training outcomes. Vision awareness training was found to significantly increase health and social care professionals' knowledge/awareness of the vision needs of people with intellectual disabilities, and their confidence in recognising signs of sights loss and recommending eye test referrals for their clients. Vision awareness training addresses a recognised barrier to effective vision health care delivery for people with intellectual disabilities.